Window on freedom : race, civil rights, and foreign affairs, 1945-1988 - Plummer, Brenda Gayle (The University of North Carolina Press, 2003)
Demonstrates how US foreign policy has been embedded in social, economic and cultural factors of domestic and foreign origin. It argues that the campaign to realize full civil rights for racial and ethnic minorities in the US is best understood in the context of competitive international relations.
Keywords: United States -- Foreign relations -- 1945-1989.; United States -- Race relations -- Political aspects.; Racism -- Political aspects -- United States -- History -- 20th century.; African Americans -- Civil rights -- History -- 20th century.; Minorities -- Civil rights -- United States -- History -- 20th century.; United States -- Foreign relations -- Developing countries.; Developing countries -- Foreign relations -- United States.; Electronic books.; Racisme -- Aspect politique -- États-Unis -- Histoire -- 20e siècle.; Noirs américains -- Droits -- Histoire -- 20e siècle.; Minorités -- Droits -- États-Unis -- Histoire -- 20e siècle.; États-Unis -- Relations extérieures -- 1945-1989.; États-Unis -- Relations raciales -- Aspect politique.; États-Unis -- Relations extérieures -- Pays en voie de développement.; Pays en voie de développement -- Relations extérieures -- États-Unis.; Livres numériques.; e-books.; POLITICAL SCIENCE -- Government -- International.; POLITICAL SCIENCE -- International Relations -- General.; African Americans -- Civil rights; Diplomatic relations; Minorities -- Civil rights; Race relations -- Political aspects; Racism -- Political aspects; Developing countries; United States; Außenpolitik; Bürgerrecht; Ethnische Beziehungen; USA; Rassenverhoudingen.; Burgerrechten.; Buitenlandse betrekkingen.; Racisme -- Aspect politique -- États-Unis -- 1945-1990.; Noirs américains -- Droits -- 1945-1990.; Minorités -- Droits -- États-Unis -- 1945- ...; États-Unis -- Relations interethniques -- Aspect politique -- 1945-1990.; Etats-Unis -- Relations interethniques -- 1945-1990.; Etats-Unis -- Relations extérieures -- Pays en voie de développement -- 1945-1990.; Pays en voie de développement -- Relations extérieures -- Etats-Unis -- 1945-1990.; 1900-1999; History